А САSЕ OF SPONTANEOUS CORONARY ARTERY DISSECTION (REVIEW AND CASE REPORT) - N. T. Vatutin; G. G. Taradin; D. V. Bort; A. V. Dmitriev; I. V. Kanisheva; I. A. Sidorenko (SINAPS LLC, 2019)
The article presents a literature review on the problem of spontaneous dissection of the coronary artery (SCAD) - tearing of its wall, not associated with atherosclerosis, trauma or iatrogenic effects leading to blood penetration between vessel layers of the artery. The consequence of this dissection is obstruction of the coronary artery due to the formation of intramural hematoma or intima damage, and myocardial ischemia with development of acute coronary syndrome, myocardial infarction or sudden cardiac death. Information on the epidemiology, pathophysiology andetiology of the disease is presented here. It was highlighted a role of arteriopathies, inflammatory diseases, pregnancy and female sex hormones, genetic causes as well as initiating and stress factors in its development. The clinic picture and diagnosis of the disease is described. It was emphasized that in addition to clinical manifestations, the traditional electrocardiogram and coronary angiography remain the standard for diagnostics of the dissection. In the treatment of SCAD, percutaneous coronary intervention with stenting of the affected artery is used, coronary artery bypass surgery and medications with regard to preference of conservative drug therapy. A special attention is paid to the features of diagnostic and therapeutic measures in pregnant and breast-feeding patients. The article also presents a clinical case of development of large-focal myocardial infarction complicated by cardiogenic shock in a young woman without risk factors for coronary heart disease in the postpartum period caused by SCAD. Diagnosis of the disease was accompanied by certain difficulties. An urgent percutaneous coronary intervention with stenting of the infarct-related coronary artery allowed rapidlyimproving and stabilizing the patient's condition.